The issues of public participation in garden design process: an analytical discourse - Mohd Yunus, Mohd.Yazid; Mohd Isa, Nor Kalsum; Nangkula, Utaberta; Ismail, Nor Atiah; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
This paper will try to reveal issues and problem in garden design process. The research applies content analysis to review some problems of public participation in garden design expressly to discourse specific issues and problems surrounding the design and space of garden design in urban fabric. The section discuss general picture concerning importance of public participation id garden design process to achieve a consensus for a better quality garden for public and community. It is anticipated that through this paper we can comprehend issues and problems of public participation in garden design process and reference frameworks in reconstructing its space for the present and the future.